Methanolysis of Vegetable Oils and Parametric Optimization - Ridzuan, Amirul Hasraff (IRC, 2015)
The exploration for environmental friendly energy is important as the main source of current world energy consumption which is fossil fuel is getting depleted and also increasing in CO2 emission. Renewable energy such as biodiesel is gain attention at now current world economic situation. Moreover, raw material and production cost are adversely affecting the economic viable of biodiesel production. Currently, more than 95% in production of biodiesel, the feedstock is from edible oil source which compete with food industry and also food processing that affecting both economic which in production of biodiesel and food industry. The problem why vegetable oil cannot directly use in diesel engine because the high viscosity contain in vegetable oil, by using transesterification reaction it can reduce the viscosity of vegetable oil. However, transesterification reaction is extremely slow due to the oil is sparingly soluble in lower alcohol and mass transfer between the two immiscible liquid is limited. The slow reaction rate of transesterification will increase the production cost of biodiesel which is also affecting increase in cost biodiesel as a fuel. Using non-edible oil such as castor oil can reduce the high cost of the feedstock because about 75% of production cost of biodiesel is come from feedstock alone. The slow reaction rate in transesterification reaction can be speed up by using reaction rate increasing technique such as microwave pre-treatment of oil and use rate enhancement agent such as phase transfer catalysis (PTC) along with conventional catalyst. In the current research work, in order to investigate transesterification of microwave pre-treated castor oil in the presence of alkaline PTC by using this two concept to utilize together. In order to design suitable transesterification reaction condition, chemical and physical properties of castor oil will be determined. The interaction and individual effects of transesterification reaction parameter will be study using design of experiment (DOE) software’s by using central composite design (CCD) of response surface methodology (RSM). After investigation of the optimum reaction condition and parametric effect for maximum yield will be established with the DOE tool.